Lawyers' identity capital. Issue 1 (2nd January 2016) - Wald, Eli
Abstract: Lawyers' commodification of personal identity is nothing new. For generations now, white male lawyers have benefitted from positive racial and gender stereotypes regarding their competence and loyalty to clients and firms to secure job offers, promotions and elevated status within the profession. Yet the concept of identity capital – the value one derives from one's personal identity – warrants attention for two related reasons. While prevalent, lawyers' use of identity capital has historically been implicit. As explicit and visible use of identity capital grows, however, lawyers must reckon with the meaning of and consequences of using identity capital in their practice. In addition, because women and minority lawyers are increasingly criticised for undermining professional standards by actively using identity capital or by passively allowing its commodification, fairness dictates that the profession comes to terms with the relationship between merit and capital. This essay examines the commodification of women and minority lawyers' personal identity in the context of the ongoing commodification of lawyers' personal identity more generally. Specifically, it explores several qualities of identity capital that ought to inform both the decision-making of individual lawyers who either actively deploy it or passively tolerate its commodification by others in representing clients and of the profession as it assesses the use of identity capital by its members: inevitable and avoidable uses of identity capital, the desirability of lawyers' commodification of personal identity, active and passive uses of identity capital, the impact of identity capital exchanges on third parties, the interplay of merit and identity capital and the appropriate terms of identity capital transactions.